Neurospora chromosomes are organized by blocks of importin alpha-dependent heterochromatin that are largely independent of H3K9me3 - Galazka, Jonathan M.; Klocko, Andrew D.; Uesaka, Miki; Honda, Shinji; Selker, Eric U.; Freitag, Michael (Genome Research, 2016)
Eukaryotic genomes are organized into chromatin domains with three-dimensional arrangements that presumably result from interactions between the chromatin constituents—proteins, DNA, and RNA—within the physical constraints of the nucleus. We used chromosome conformation capture (3C) followed by high-throughput sequencing (Hi-C) with wild-type and mutant strains of Neurospora crassa to gain insight into the role of heterochromatin in the organization and function of the genome. We tested the role of three proteins thought to be important for establishment of heterochromatin, namely, the histone H3 lysine 9 methyltransferase DIM-5, Heterochromatin Protein 1 (HP1), which specifically binds to the product of DIM-5 (trimethylated H3 lysine 9 [H3K9me3]), and DIM-3 (importin alpha), which is involved in DIM-5 localization. The average genome configuration of the wild-type strain revealed strong intra- and inter-chromosomal associations between both constitutive and facultative heterochromatic domains, with the strongest interactions among the centromeres, subtelomeres, and interspersed heterochromatin. Surprisingly, loss of either H3K9me3 or HP1 had only mild effects on heterochromatin compaction, whereas dim-3 caused more drastic changes, specifically decreasing interactions between constitutive heterochromatic domains. Thus, associations between heterochromatic regions are a major component of the chromosome conformation in Neurospora, but two widely studied key heterochromatin proteins are not necessary, implying that undefined protein factors play key roles in maintaining overall chromosome organization.